Reviewer Acknowledgement - Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2022)
The following professionals deserve special recognition for the time and effort they have recently contributed by serving as reviewers for the Canadian Journal of Counselling and Psychotherapy.